The Impact of Risk-Based ESG Scores, Return on Asset (ROA) and Return on Equity (ROE) on Firm Value - Rahmania, Thriyani; Ermawati, Wita Juwita; Suprayitno, Gendut (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2025)
The urgency to understand the impact of risk-based Environmental, Social, and Governance (ESG) and financial factors on firm value remains high, especially for listed companies in Indonesia. Indonesia is a disaster-prone country. World Risk Report in 2021 shows that Indonesia ranks 38th out of 181 countries in the "High" disaster risk category, with an index score of 10.67, and in the "Very High" Risk Exposure category, with an index score of 21.30. This study examines the impact of risk-based ESG scores, ROA, and ROE on firm value. Using a quantitative and purposive sampling method, the research applies a panel data regression analysis of 300 observations from companies listed on the Indonesian Stock Exchange (2019–2023) with Sustainalytics ESG Risk Ratings. While the combined effect of ESG risk scores, ROA, and ROE significantly influenced firm value, partial analysis revealed no individual significance. The results underscore the need for Indonesian firms to integrate ESG practices holistically to enhance stakeholder trust and financial outcomes, while regulators should refine policies to incentivize ESG risk mitigation, particularly in high-risk sectors.